KNOWLEDGE OPINIONS LEGAL ENFORCEMENT AND FACTORS RELATED TO LEGAL ENFORCEMENT OF MEDICAL FACILITIES ACT AMONG REGULATORY OFFICERS IN PROVINCIAL HEALTH OFFICES - Sareekhajohnjaru, Kanokkan; Lochidamnuay, Surasit (Thai Bulletin of Pharmaceutical Sciences, 2025)
This cross-sectional analytical study aimed to assess the knowledge, opinions, law enforcement practices, and associated factors related to the enforcement of the Medical Facilities Act among regulatory officers in provincial areas. The study population comprised officers responsible for the supervision and regulation of medical facilities within the Consumer Protection and Public Health Pharmacy Division at the Provincial Public Health Offices in all 76 provinces across Thailand (one officer per province). Data were collected via mailed questionnaires during July–August 2024, with a total of 70 responses received, yielding a response rate of 92.11%. Data were analyzed using descriptive statistics, chi-square tests, and Fisher’s exact tests at a significance level of 0.05. The results showed that most officers had a moderate level of knowledge (60.0%) and expressed a high level of agreement (98.6%) with key decision-making factors in law enforcement, particularly the offender’s intent, business size, and prior offenses (98.6%, 95.7%, 92.9% respectively). Opinions regarding the administrative fine mechanism were at a moderate level (51.4%). Law enforcement practices were found to be high in the areas of inspection, seizure, and prosecution (100.0%, 80.0%, 80.0% respectively), whereas the application of the administrative fine mechanism remained limited (41.4%). Further analysis revealed that the level of knowledge among officers was the only factor significantly associated with the overall level of law enforcement (p-value = 0.004). Therefore, it is necessary to continuously promote and develop legal knowledge, both theoretical and practical, among regulatory officers, and to establish clear, comprehensive, and systematic enforcement guidelines to strengthen the efficiency of medical facility regulation at the provincial level.